2016 IEEE Global Humanitarian Technology Conference (GHTC) 2016
DOI: 10.1109/ghtc.2016.7857268
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability analysis off-grid community solar PV projects in Malawi

Abstract: The sustainability challenges of off-grid community energy projects using solar photovoltaics in Malawi have been widely acknowledged. However, little evidence has been produced regarding the factors that affect the sustainability of these projects. This paper presents the results of a nationwide study of community solar PV project sustainability in Malawi. The concept of sustainability as a holistic measure is defined and captured through field survey at 43 projects. A multi-factor scoring technique provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The project design was strongly influenced by evaluations of previous projects in Malawi [9] [10] and employed the common thematic classification of sustainability pillars: economic, technical, social, organisational and environmental [11]. A high level of community capacity building with clear roles and responsibilities for management and operations was prioritised along with a strong technical oversight in the demand assessment and system design stages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The project design was strongly influenced by evaluations of previous projects in Malawi [9] [10] and employed the common thematic classification of sustainability pillars: economic, technical, social, organisational and environmental [11]. A high level of community capacity building with clear roles and responsibilities for management and operations was prioritised along with a strong technical oversight in the demand assessment and system design stages.…”
Section: Methodsmentioning
confidence: 99%
“…Rural energy projects in Malawi typically include aspects of community ownership and operation, and target a public facility such as a primary school or health centre. However, despite the high impact, many of these projects have fallen short of sustainability expectations [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a solar PV sustainability study carried out in 2014 found that for lighting loads, only 42% of 188 rooms surveyed throughout Malawian public service institutions were meeting usage expectations [23]. This implies two opportunities for RM technology which are addressed in this paper: firstly, to better understand how off-grid PV systems themselves operate in Malawi and, secondly, to use RM technology to better improve sustainability of these systems.…”
Section: Mreap's Strategic Energy Project In Solar Pv the Malawimentioning
confidence: 98%
“…An evaluation of 12 case studies of community renewable energy projects in 2012 cited insufficient financial models, unclear management structures, and limited local technical capacity [15] as being responsible for their poor sustainability. Similarly, a nationwide evaluation of 43 projects in 2015 found many projects at various states of failure due to poor technical design, inadequate revenue, and low operator skill levels [16].…”
Section: Malawian Electricity Landscapementioning
confidence: 99%
“…Data gathering took place in two phases. The first phase, undertaken in 2014, surveyed 43 projects and evaluated the sustainability of existing PV projects [16]. The original study design intended to have additional sites, but this was limited due to implementation program scope and reporting needs.…”
Section: Data Sources Community Electricity Project Datamentioning
confidence: 99%